Effects of pitching motion profile on energy harvesting performance of a semi-active flapping foil using immersed boundary method. (1st September 2018) - Li, Weizhong; Wang, Wen-Quan; Yan, Yan; Tian, Fang-Bao
Abstract: Effects of pitching motion profile on energy harvesting performance of a semi-active flapping foil are numerically studied using immersed boundary method. Firstly, the numerical method is validated by considering a sinusoidal pitching semi-active flapping foil at Re = 1000 and a uniform flow over a stationary foil at Reynolds number Re = 500. Then, we consider a semi-active flapping foil with Reynolds number Re = 1000 and study the effect of sine-like and cosine-like pitching motion on the energy harvesting performance at reduced frequency f ∗ = 0.16. We study the pitching, with a gradual change from a sinusoid/cosinusoid to a square wave as β is increased from one. We found that increasing the value of β is ineffective to enhance energy harvesting efficiency for sine-like pitching motion, which is in agreement with the results of Deng et al. (2015) and Teng et al. (2016), however, for cosine-like pitching motion, the highest energy harvesting efficiency of 51.81% is recorded for pitching amplitude θ 0 = 60° and β = 2.0. Meanwhile, we observed that cosinusoidal pitching motion is more efficient for energy harvesting than sinusoidal pitching motion, and non-cosinusoidal pitching motion can enhance the harvesting efficiency compared to cosinusoidal pitching motion. In detail, we report the different performances of the sine-like and cosine-like pitching motion to study the mechanical mechanism of enhancing energy harvesting efficiency. Highlights: Semi-active flapping foil is simulated using immersed boundary method, easy to implement and enough accuracy. A semi-active flapping foil with sine-like and cosine-like pitching motion was studied and compared. For cosine-like pitching motion, the highest energy harvesting efficiency of 51.81% is recorded.